Multivalent IDP assemblies: Unique properties of LC8‐associated, IDP duplex scaffolds. Issue 19 (29th July 2015) - Clark, Sarah A.; Jespersen, Nathan; Woodward, Clare; Barbar, Elisar
Abstract : A wide variety of subcellular complexes are composed of one or more intrinsically disordered proteins (IDPs) that are multivalent, flexible, and characterized by dynamic binding of diverse partner proteins. These multivalent IDP assemblies, of broad functional diversity, are classified here into five categories distinguished by the number of IDP chains and the arrangement of partner proteins in the functional complex. Examples of each category are summarized in the context of the exceptional molecular and biological properties of IDPs. One type – IDP duplex scaffolds – is considered in detail. Its unique features include parallel alignment of two IDP chains, formation of new self‐associated domains, enhanced affinity for additional bivalent ligands, and ubiquitous binding of the hub protein LC8. For two IDP duplex scaffolds, dynein intermediate chain IC and nucleoporin Nup159, these duplex features, together with the inherent flexibility of IDPs, are central to their assembly and function. A new type of IDP–LC8 interaction, distributed binding of LC8 among multiple IDP recognition sites, is described for Nup159 assembly.